2023
DOI: 10.3390/ijms242115972
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Approach for Secondary Prevention of Uterine Fibroids (The ESCAPE Approach)

Somayeh Vafaei,
Michał Ciebiera,
Mervat M. Omran
et al.

Abstract: Uterine fibroids (UFs) are common tumors in women of reproductive age. It is imperative to comprehend UFs’ associated risk factors to facilitate early detection and prevention. Simple relying on surgical/pharmacological treatment of advanced disease is not only highly expensive, but it also deprives patients of good quality of life (QOL). Unfortunately, even if the disease is discovered early, no medical intervention is traditionally initiated until the disease burden becomes high, and only then is surgical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 243 publications
0
5
0
Order By: Relevance
“…Consuming bell peppers can provide a significant boost to the immune system, helping the body fight off infections and illnesses. Moreover, bell peppers contain antioxidants, which are beneficial compounds that can help prevent the growth of UFs by combating oxidative stress and reducing inflammation [ 10 , 55 ].…”
Section: Optimal Dietary Choices To Consider (Food Modifications)mentioning
confidence: 99%
See 4 more Smart Citations
“…Consuming bell peppers can provide a significant boost to the immune system, helping the body fight off infections and illnesses. Moreover, bell peppers contain antioxidants, which are beneficial compounds that can help prevent the growth of UFs by combating oxidative stress and reducing inflammation [ 10 , 55 ].…”
Section: Optimal Dietary Choices To Consider (Food Modifications)mentioning
confidence: 99%
“…Clinical trials have reported significant reductions in UF size with long-term vitamin D supplementation, with an excellent safety profile and no reported adverse events [ 71 , 72 ]. The use of vitamin D (4000 IU/day) was introduced in our previous ESCAPE approach to manage UFs [ 10 ].…”
Section: Optimal Dietary Choices To Consider (Food Modifications)mentioning
confidence: 99%
See 3 more Smart Citations